2004
DOI: 10.1097/00001888-200409000-00018
|View full text |Cite
|
Sign up to set email alerts
|

Integrating an Evidence-Based Medicine Rotation into an Internal Medicine Residency Program

Abstract: An EBM elective rotation was successfully integrated into a residency program. This multifaceted educational approach with an "on-the-ward" EBM resident, may improve the EBM knowledge and skills of targeted students and residents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 16 publications
1
44
0
Order By: Relevance
“…This finding was similar to previously published studies [5][6][7][8]. Hester et al incorporated literature evaluation exercises in a primary care advanced pharmacy practice rotation and concluded that it had increased the students' understanding and strengthened their therapeutic recommendations [5].…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…This finding was similar to previously published studies [5][6][7][8]. Hester et al incorporated literature evaluation exercises in a primary care advanced pharmacy practice rotation and concluded that it had increased the students' understanding and strengthened their therapeutic recommendations [5].…”
Section: Resultssupporting
confidence: 89%
“…A survey was administered as a pre and post-test to assess the effectiveness of and attitude towards EBM rotation. There was a noticeable favorable attitude in the surveys of medical residents towards EBM rotation [8]. …”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…4 Historically, the majority of EBM courses have been seminar series, workshops, or "short courses". [5][6][7][8] Courses of EBM instruction integrated longitudinally with clinical practice are rare, [9][10][11] despite limited but supportive evidence in favor of such teaching approaches to EBM. 12 Objective assessment of EBM skills is essential, as selfreported skills correlate poorly with actual EBM knowledge.…”
Section: Introductionmentioning
confidence: 99%